2002
DOI: 10.1080/0959523021000002732
|View full text |Cite
|
Sign up to set email alerts
|

Peer overdose resuscitation: multiple intervention strategies and time to response by drug users who witness overdose

Abstract: One hundred and thirty-five drug users in contact with treatment services in Scotland and England were interviewed about their experiences of witnessing overdoses - both overdoses resolved successfully and those leading to death - and actions taken to effect resuscitation. One hundred and four (77%) had witnessed a mean of 11.5 overdoses, of whom 41 (30.4% of the study sample) had witnessed an average of 4.2 fatal overdoses. A wide range of actions was reported at the most recent witnessed overdose, the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
(25 reference statements)
1
23
2
Order By: Relevance
“…We also examined the circumstances of these overdoses, and found that more than three-quarters of overdoses occurred in a home situation and in the company of others (see Table 2) [31,32], hence apparently suitable for the training and naloxone provision that we were considering. We also conducted 'market research'-pre-launch testing of the acceptability of the proposed intervention with the target population of drug users themselves-and found high levels of approval and interest [32,33] and also high levels of previous active intervention, even though the interventions were often wrong [33][34][35].…”
Section: Before Trainingmentioning
confidence: 99%
“…We also examined the circumstances of these overdoses, and found that more than three-quarters of overdoses occurred in a home situation and in the company of others (see Table 2) [31,32], hence apparently suitable for the training and naloxone provision that we were considering. We also conducted 'market research'-pre-launch testing of the acceptability of the proposed intervention with the target population of drug users themselves-and found high levels of approval and interest [32,33] and also high levels of previous active intervention, even though the interventions were often wrong [33][34][35].…”
Section: Before Trainingmentioning
confidence: 99%
“…Survey-based studies have indicated that the prevalence of witnessing among drug users may range between 24% and 94% (Baca and Grant, 2007; Bennett and Higgins, 1999; Best et al, 2002; Davidson et al, 2002; Kaye and Darke, 2004; Pollini et al, 2006a; Tracy et al, 2005). These data suggest that drug users may frequently be witnesses at the overdoses of other drug users.…”
Section: Introductionmentioning
confidence: 99%
“…Given that many drug overdoses are never reported to emergency health services, drug users themselves may be made aware of overdose problems before anyone else becomes alerted to them. Although most overdoses are witnessed by others, bystanders will delay or neglect to seek appropriate medical assistance for reasons such as fear of arrest [37,38]. Studies indicate that many overdoses do not involve calling the ambulance or going to the hospital.…”
Section: Discussionmentioning
confidence: 99%